Assessments Of Awkward Postures Associated With Biomechanical Forces And Muscle Activations During Collecting Oil Palm Fresh Fruit Bunches - M.Ghazali, Nor Maisarah (Universiti Sains Malaysia, 2021)
The purpose of this study is to present the ergonomic risks in collecting fresh fruit bunches (FFBs) with the assessment of the lumbar spine related to trunk flexions and rotations, then comparing them to the existing literature. The experiments of different types of FFBs loading were designed including the manual loading of twisted body and bent forward body, the loading spike was used to evaluate the risks in loading activities at different heights, and the unloading fully loaded wheelbarrow task. The ergonomic risks had been evaluated using REBA score and 3DSSPP software. These approaches were used to stimulate the results for different postures in each task. The comparison between the twisting and bending torso showed a pressure difference of disc L5/S1 where the twisted body more harmful compared to bending body. It was due to the trunk flexion and rotation that lead to the compression and shear forces. Even the trunk flexions of bending torso were higher than the twisted, it did not very harmful to the body since it only involved the trunk flexion compared to the twisted body which involved both trunk flexions and rotations. Besides twisting and bending torso, the squatting and half-squatting posture also in a high ergonomic risk. While loading FFBs using loading spikes, the higher the heights exerted more effort to lift the FFBs. Hence, increasing the ergonomic risk since involving the over shoulder lifting. Both recruited subject complaint that they felt discomfort and pains on the shoulder, arm and lower back.